Enhancing neuroimaging genetics through meta-analysis for Tourette syndrome (ENIGMA-TS): A worldwide platform for collaboration - Paschou, Peristera; Jin, Yin; Müller-Vahl, Kirsten; Möller, Harald E.; Rizzo, Renata; Hoekstra, Pieter J.; Roessner, Veit; Mol Debes, Nanette; Worbe, Yulia; Hartmann, Andreas; Mir, Pablo; Cath, Danielle; et al. (Frontiers in Psychiatry, 2022)
Tourette Syndrome (TS) is characterized by multiple motor and vocal tics and high comorbidity rates with other neuropsychiatric disorders. Obsessive Compulsive Disorder (OCD), Attention Deficit Hyperactivity Disorder (ADHD), Autism Spectrum Disorders (ASD), Major Depressive Disorder (MDD) and Anxiety Disorders (AXD) are among the most prevalent TS comorbidities. To date, studies on TS brain structure and function have been limited in size with efforts mostly fragmented. This leads to low statistical power, discordant results due to differences in approaches, and hinders the ability to stratify patients according to clinical parameters and investigate comorbidity patterns. Here, we present the scientific premise, perspectives, and key goals that have motivated the establishment of the ENIGMA-TS Working Group (Enhancing Neuroimaging Genetics through Meta-Analysis for TS). ENIGMA-TS is an international collaborative effort bringing together a large network of investigators aiming to understand brain structure and function in TS and dissect the underlying neurobiology that leads to observed comorbidity patterns and clinical heterogeneity. Previously collected TS neuroimaging data will be analyzed jointly and integrated with genomic data as well as equivalently large and already existing studies of highly comorbid OCD, ADHD, ASD, as well MDD, and AXD. Our work highlights the power of collaborative efforts and transdiagnostic approaches and points to the existence of different TS subtypes. ENIGMA-TS will offer large-scale, high-powered studies that will lead to important insights towards understanding brain structure and function and genetic effects in TS and related disorders as well as biomarkers that could help inform improved clinical practice.